Jurnal ILMU KOMUNIKASI: THE EMERGENCE OF THE PHILIPPINE "ANTI-MEDIA": THE DUTERTE FACTOR - Jermaine Vistro Beltran (PRODI Ilmu Komunikasi UAJY, 2017)
The Philippine news media is perceived to be the freest in Asia. However, it also has its faults which its audiences have noticed. This study was aimed at exploring the factors which have lead to the audience’s dissent and subsequent emergence of an online anti-media movement. A qualitative research method was utilized where in social media posts and websites were analyzed with the Agenda Setting Theory to explain the frames being made by the mainstream and anti-media. The results showed factors such as the internet and its tools in creating a new virtual community.